Pendekatan Konseling Psikoanalisa Dalam Dunia Pendidikan: Studi Literatur - Hanif Aftiani; Budi Purwoko; Bakhrudin Al Habsy (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Towards a Golden Indonesia 2045. The world of education is required to develop optimally in order to meet human resources in the future. Today's high school level students are potential leaders in that era. These demands and challenges can cause anxiety in students in addition to increasingly complex adolescent problems. Psychoanalytic counseling can be a method to help students deal with personal problems. reshaping individual character structures by creating unconscious awareness in students. The literature review technique was used in the composition of this piece. Literature review is a way to find, read, and comprehend written works that have been produced during the last ten years. Definitions, counseling stages, counseling procedures, and the pros and cons of the psychoanalytic counseling approach are all part of the research's findings within the psychoanalytic theoretical framework.